2010
DOI: 10.1016/j.ctrv.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box M1 transcription factor: A novel target for cancer therapy

Abstract: FoxM1 signaling has been reported to be associated with carcinogenesis. Therefore, the FoxM1 may represent a novel therapeutic target, and thus the development of agents that will target FoxM1 is likely to have significant therapeutic impact on human cancer. This review describes the mechanisms of signal transduction associated with FoxM1 and provides emerging evidence in support of its role in the carcinogenesis. Further, we summarize data on several FoxM1 inhibitors especially “chemopreventive agents” and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 72 publications
2
114
0
Order By: Relevance
“…Furthermore, depletion of FoxM1 has been shown to cause mitotic spindle defects, cell cycle arrest, chromosome misaggregation and mitotic catastrophe [12,13]. Recent reports have also demonstrated that FoxM1 plays important roles in cellular developmental pathways including the maintenance of homeostasis between cell proliferation and apoptosis and as a result, alterations in FoxM1 signaling has been reported to be associated with carcinogenesis and tumor aggressiveness [8,9,14] cancer, glioblastomas, prostate cancer, basal cell carcinomas and pancreas cancer [15][16][17][18][19]. These results give rise to some questions about the role of FoxM1 in pathogenesis of leukemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, depletion of FoxM1 has been shown to cause mitotic spindle defects, cell cycle arrest, chromosome misaggregation and mitotic catastrophe [12,13]. Recent reports have also demonstrated that FoxM1 plays important roles in cellular developmental pathways including the maintenance of homeostasis between cell proliferation and apoptosis and as a result, alterations in FoxM1 signaling has been reported to be associated with carcinogenesis and tumor aggressiveness [8,9,14] cancer, glioblastomas, prostate cancer, basal cell carcinomas and pancreas cancer [15][16][17][18][19]. These results give rise to some questions about the role of FoxM1 in pathogenesis of leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The newly developed targeted therapies, if proven effective, may eventually allow us to minimize conventional antineoplastics and the associated toxicities, while maximizing survival and minimizing relapse [5]. The Forkhead box protein M1 (FoxM1) belongs to the Forkhead superfamily of transcription factors which all share an evolutionary conserved 'winged helix' DNA-binding domain [8,9]. The expression of FoxM1 is restricted to cells that are proliferating and its expression is negatively regulated in terminally differentiated cells.…”
Section: Introductionmentioning
confidence: 99%
“…A number of anticancer drugs used in the clinic, function through modulation of cell cycle. In addition to direct targeting of cell cycle regulatory factors for anticancer therapy, genes such as FoxM1 that modulate cell cycle machinery (Wang et al, 2010a), have also been targeted in breast cancer models leading to the inhibition of proliferation and invasion of aggressive cells (Ahmad et al, 2010). Furthermore, the anticancer properties of natural non-toxic compounds are increasingly being realized.…”
Section: Discussionmentioning
confidence: 99%
“…All Fox members, being classified as FOXA to FOXR (15), Fox molecules play critical roles in a variety of physiologic (16) or pathologic processes such as cancer, as tumor suppressors (17)(18)(19). Particularly, FOXM1 was identified to be oncogenic in pancreatic cancer, and is associated with poor prognosis and pathologic stage of PADC (20,21), whereas, FOXL1 has recently been recognized as a tumor suppressor in PADC (22).…”
Section: Introductionmentioning
confidence: 99%